Synthesis and antimycobacterial screening of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline derivatives - Thakare, Prashant P.; Walunj, Yogesh; Chavan, Abhijit; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Journal of Heterocyclic Chemistry, 2020)
A new series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline (6a-t) have been synthesized by a click reaction of 4-(4-ethynyl-1-phenyl-1H-pyrazol-3-yl)quinoline (4a-d) with a substituted benzyl azide (5a-e). The starting alkyne derivatives4a-dare obtained from Bestmann-Ohira reaction of 1-phenyl-3-(quinolin-4-yl)-1H-pyrazole-4-carbaldehyde and dimethyl(1-diazo-2-oxopropyl)phosphonate. The newly synthesized compounds are screened againstM. tuberculosisH37Ra dormant and active,Escherichia coli,Pseudomonas fluorescence,Staphylococcus aureusandBacillus subtilisstrains at 30 mu g/mL concentration. Most of the screened compounds showed good to moderate antibacterial activity againstS. aureus,B. subtilis, andMycobacterium tuberculosisH37Ra strains. The synthesized derivatives of quinolinyl-pyrazole-4-carbaldehyde and quinolinyl-pyrazole-4-ethyne reportd good to moderate activity against both strains ofM. tuberculosisH37Ra. Ten derivatives of quinolinyl-pyrazole presented good activity againstB. subtilis. These results suggested that further optimization and development of quinolinyl-pyrazolyl-1,2,3-triazole moeity could serve as lead compounds for antimycobacterial activity.